Winning strategies: applying ancient Chinese wisdom in business and management - Khoo Kheng-Hor (Subang Jaya: Pelanduk Publications, 2000)
China's vast storage ofinspirational disparate intelectual thoughts
Includes index
Keywords: Ethics -- China -- History; China -- Civilization; Ethics, Chinese